Fear Network Model in Panic Disorder: The Past and the Future - Lai, Chien-Han (Psychiatry Investig, 2019)
The core concept for pathophysiology in panic disorder (PD) is the fear network model (FNM). The alterations in FNM might be linked with disturbances in the autonomic nervous system (ANS), which is a common phenomenon in PD. The traditional FNM included the frontal and limbic regions, which were dysregulated in the feedback mechanism for cognitive control of frontal lobe over the primitive response of limbic system. The exaggerated responses of limbic system are also associated with dysregulation in the neurotransmitter system. The neuroimaging studies also corresponded to FNM concept. However, more extended areas of FNM have been discovered in recent imaging studies, such as sensory regions of occipital, parietal cortex and temporal cortex and insula. The insula might integrate the filtered sensory information via thalamus from the visuospatial and other sensory modalities related to occipital, parietal and temporal lobes. In this review article, the traditional and advanced FNM would be discussed. I would also focus on the current evidences of insula, temporal, parietal and occipital lobes in the pathophysiology. In addition, the white matter and functional connectome studies would be reviewed to support the concept of advanced FNM. An emerging dysregulation model of fronto-limbic-insula and temporooccipito-parietal areas might be revealed according to the combined results of recent neuroimaging studies. The future delineation of advanced FNM model can be beneficial from more extensive and advanced studies focusing on the additional sensory regions of occipital, parietal and temporal cortex to confirm the role of advanced FNM in the pathophysiology of PD.